Working memory biases early object discrimination and parietal activity during attentional selection. (December 2022) - Wang, Min; Yang, Ping; Zhang, Tingting; Li, Wenjuan; Zhang, Junjun; Jin, Zhenlan; Li, Ling
Abstract: The contents of working memory (WM) guide visual attention, but the neural mechanisms underlying WM biases remains unclear. Here, we used simultaneous electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) approaches to characterize the timing and location of the neural response underlying WM guidance during a visual search task. Behaviorally, we observed faster search performance when the WM contents matching targets (valid) compared to when WM contents did not reappear (neutral). The EEG data showed similar benefit effects of posterior N1 component, in which targets induced larger N1 amplitudes in the valid condition than in the neutral condition. Interestingly, the fMRI activation in left supramarginal gyrus (SMG)/inferior parietal lobule (IPL) and bilateral occipital cortex was lower in the valid compared to neutral conditions. Importantly, the magnitude of the increased N1 activity and the decreased fMRI activity in the left SMG/IPL predicted the extent of search improvement at an individual subject level. These results suggest that information held in WM enhances early object discrimination during attentional selection, and the left SMG/IPL may be a critical region in mediating goal-directed processing under WM biases in human visual attention.